Canaryseed Crop - Cogliatti, Maximiliano (2012)
Canaryseed (Phalaris canariensis L.) is a graminaceous crop species with production practices and cycle similar to those of other winter cereal crops such as spring wheat (Triticum aestivum L.) and oat (Avena sativa L.). Currently its grains are used almost exclusively as feed for birds, alone or mixed with other grains like millet, sunflower seed, and flaxseed. Canaryseed is a genuine cereal with a unique composition that suggests its potential for food use. P. canariensis is cultivated in many areas of temperate climates. Currently, its production is concentrated in the southwestern provinces of Canada (Alberta, Saskatchewan and Manitoba) and on a smaller scale in Argentina, Thailand and Australia. Globally it is considered to be a minor crop with regional relevance, with a production about of 250000 tonnes per year, which restricts private investment and public research on its genetic and technological improvement. For this reason, the type of crop management that is applied to this species largely depends on innovations made in other similar crops. This work provides an updated summary of the available information on the species: its requirements, distribution, genetic resources, cultivation practices, potential uses, marketing and other topics of interest to researchers and producers.